Word-Processing and the Fifth-Grade Student -- Getting the Write Idea - Kelly, Karen S. (My University, 2002)
The purpose of the research was to determine whether word processors enhanced or impeded students' success in carrying out the steps of the writing process. The instructional unit was taught to four intact groups of thirty-eight elementary school students, comparatively ranked into high- to-average and low-to-at-risk ability groups over a four-week time span. Eight teachers, as well as the thirty-eight students completed the activities for the unit. This qualitative study included observation, pre and postwriting assessments, editing and revision checklists, interview, and a post- intervention survey. Each teacher participant completed a survey assessing teacher attitudes and perceptions towards using word processing in the writing process. All students completed a similar, but more comprehensive, study at the end of the unit. Findings suggest that teachers considered word processing a highly favorable option for teaching the writing process, but most indicated that they currently take little advantage of the technology. Student participants additionally expressed favorable attitudes towards word processing in the writing process, and chose it over paper-and-pencil writing as the preferred method. Student participants additionally completed pre- and post- writing assessments. The majority of the students showed drastic improvements between the pre and posttests. Posttest comparisons between the groups showed that the word processor did enhance performance with the high ability group. The word processor, however, impeded the lower ability groups, due to lack of keyboarding skills, difficulties with spelling and sentence structures, and intimidation by the technology. The results of the study were communicated to the learning community through a meeting with teachers and administrators. Those present supported keyboarding instruction in the younger grades to help older elementary school students to already have these necessary skills intact, and further alleviate the intimidation by the technology.
Keywords: Word processors; Elementary school students; Keyboarding skills